Comparative analysis of Neptunea cumingii growth, related digestive and immune enzyme indicators, and liver transcriptome under different feeding conditions - Ge, Xinfan; Zhao, Jing; Liang, Zhongde; Chi, Qinghong; Mao, Junxia; Wang, Xubo; Chang, Yaqing; Hao, Zhenlin (Frontiers in Marine Science, 2022)
Neptunea cumingii is a carnivorous snail with a very high market value, but it cannot be cultivated on a large scale at present due to the lack of an appropriate artificial feed. In this study, we fed N. cumingii four kinds of diets (Cristaria plicata meat, Chlamys farreri mantle, Mytilus edulis meat, and artificial feed) for 90 days and then measured growth indexes and digestive and immune enzyme indexes. We also subjected liver samples to transcriptome sequencing to detect significant differences among the four groups at the transcriptome level. The survival rate of N. cumingii fed with each type of feed was > 90%. The weight, shell length, shell height, and weight gain of the N. cumingii in the C. plicata meat group were significantly higher than those of the other treatment groups, while the values in the artificial feed group were significantly lower than those of the other treatment groups. The superoxide dismutase, catalase, amylase, protease, and lipase activities were higher in the stomach, intestine, and liver of snails in the C. plicata meat feeding group than in those of the other treatment groups, and they were significantly higher than those of the artificial feed group (p < 0.05); the opposite was true for malondialdehyde content. A total of 3407 differentially expressed genes (DEGs) were found in the M. edulis meat group vs. C. plicata meat group comparison. A total of 3422 DEGs genes were identified in the artificial feed group vs. C. plicata meat group comparison. A total of 3,929 DEGs were found in the C. plicata meat group vs. C. farreri mantle group comparison. Through Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis, we found the DEGs in the liver of N. cumingii fed with the different diets were mainly enriched in the energy metabolism, growth, and immunity pathways. Our results indicated that among the four diets tested, C. plicata meat had the best effect on N. cumingii, and they provided an important reference for identification of suitable diets for the development of N. cumingii artificial breeding.